2018
DOI: 10.1093/dnares/dsy042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of early-stage female germ cells revealed by RNA sequencing of low-input cells and analysis of genome-wide DNA methylation

Abstract: High-throughput stage-specific transcriptomics provides an unbiased approach for understanding the process of cell development. Here, we report transcriptome analysis of primordial germ cell, female germline stem cell (FGSC), germinal vesicle and mature oocyte by performing RNA sequencing of freshly isolated cells in mice. As expected, these stages and gene-expression profiles are consistent with developmental timing. Analysis of genome-wide DNA methylation during female germline development was used for confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…Among these, hif1an , which is related to Notch signaling, could be a potential marker for female germline cells. Our findings indicated that FGSCs belong to ASCs in the high-order organization, and further confirmed the existence of FGSCs, consistent with the previous reports for cellular and molecular characteristic 47,44,45 .…”
Section: Discussionsupporting
confidence: 92%
“…Among these, hif1an , which is related to Notch signaling, could be a potential marker for female germline cells. Our findings indicated that FGSCs belong to ASCs in the high-order organization, and further confirmed the existence of FGSCs, consistent with the previous reports for cellular and molecular characteristic 47,44,45 .…”
Section: Discussionsupporting
confidence: 92%
“…Time course RNA sequencing has been widely used to study cellular differentiation (Ma et al, 2018), tissue development (Cardoso-Moreira et al, 2019), and aging (Baumgart et al, 2016). We provide a new insight on the transcriptome changes in chickens between different development stages of BM and AF.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA is a powerful tool for identifying genes that are associated with the phenotypes under study ( Langfelder and Horvath, 2008 ). WGCNA can also be used to identify tissue- or stage-specifically expressed gene modules ( Gao et al, 2018 ; Ma et al, 2018 ). To investigate the expressed genes in different developmental stages, we performed the WGCNA for BM and AF tissues as a consensus data set.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, Kunming mice were chosen to construct the POF models in view of their excellent reproductive capacity and adaptability. Previous studies [45,46] have shown that FGSCs not only present in the ovaries of Kunming mice, but also exist in CD-1 and C57 mice. We believe RES is also as effective in other strains.…”
Section: Discussionmentioning
confidence: 99%